Constructibility of retrofitting methods applicable to selected unreinforced masonry structures - Lucas, Ma. Lorellie M.; Marasigan, Kristian Elijah D.
The seismic vulnerability of old structures poses a great risk to the preservation of heritage structures in the Philippines. Hence, there is a need in examining the vulnerabilities of a certain building and then recommend feasible retrofitting techniques in order to seismically strengthen it. In this study, a vulnerability assessment was employed before deducing the most applicable retrofitting method. The evaluation consisted of Rapid Visual Screening of Buildings for Potential Seismic Hazards: A Handbook, Third Edition or also known as FEMA P-154 in which a Level 1 Data Collection Form was accomplished and supplied with pertinent data including seismic performance data documentation. The findings showed both structures need further Detailed Structural and Nonstructural Evaluation. An additional vulnerability assessment focusing on the critical parts of each structure followed and thus pointed out the major concerns. Afterwards, probable retrofitting techniques were listed and ranked according to criteria - material characterization, construction methodology, and economy - considering the structural deficiencies involved. Repointing garnered the highest rating in addressing material degradation and masonry disjointing, tie rods and epoxy injection for the cracks, and shotcrete or reinforced plaster for keying-induced surface deterioration of stones.